2017
DOI: 10.1177/2049463717709641
|View full text |Cite
|
Sign up to set email alerts
|

Growing pains: understanding the needs of emerging adults with chronic pain

Abstract: Background: Emerging adulthood (18-30 years), in the Western world, is often a time of identity development and exploration, focusing on areas of work, relationships and education. Individuals with chronic illnesses, such as chronic pain, may be more vulnerable to facing challenges during this time. This study aims to investigate the needs of young adults (YAs) attending a tertiary level National Health Service (NHS) Pain Management Programme (PMP) Service in the United Kingdom; exploring how these needs may t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 48 publications
(60 reference statements)
0
29
0
Order By: Relevance
“…Because the majority of significant interactions testing age as a moderator were found for depression, it is possible that age-tailored interventions targeting co-morbid depression may be particularly relevant. Qualitative studies have revealed that young adults with chronic pain present with unique treatment needs; for example, young adults have indicated the need to incorporate content related to the impact of chronic pain on emotional health and transition to college or full-time work (Stinson et al, 2013;Twiddy et al, 2017). However, there has been limited testing of treatments tailored to this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Because the majority of significant interactions testing age as a moderator were found for depression, it is possible that age-tailored interventions targeting co-morbid depression may be particularly relevant. Qualitative studies have revealed that young adults with chronic pain present with unique treatment needs; for example, young adults have indicated the need to incorporate content related to the impact of chronic pain on emotional health and transition to college or full-time work (Stinson et al, 2013;Twiddy et al, 2017). However, there has been limited testing of treatments tailored to this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Back pain (BP) is a significant public health problem. 15 Recent studies 6,7 suggested that the prevalence of BP has been increasing in adolescents; this can cause a range of disabilities that may persist into adulthood. 810 Therefore, the causes of BP must be investigated with a focus on adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Back pain (BP), defined as "pain within the cervical, thoracic and/or lumbar areas" [1][2][3], is a significant public health problem [1][2][3][4][5][6][7]. Recent studies [8][9][10] suggest that the prevalence of BP, including acute, chronic, specific, and non-specific conditions, has been increasing among adolescents; it can cause a range of functional limitations that may persist into adulthood [11][12][13].…”
Section: Introductionmentioning
confidence: 99%